Національні еліти у системі соціального управління і трансформаційні міфологеми - Полисаєв, О.П.; Шедяков, В.Є. (№8, 2007)
The characteristic features and development level of the national elitism development as transformation of Ukrainian society are analyzed. The social and cultural determinants of post-soviet elitism creation, specifics of its formation in the social environment with predominant egalitarian mythologemes are reviewed. The attempt is made to investigate complicated processes of mutual resonating of society and its elitism in the context of a part of USSR to the national state growth and of agricultural and industrial manufacturing society to information society.